Splenium infarction presenting as incongruous homonymous hemianopsia: A case report and narrative review - Kumar, Shivank; Bhartiya, manish (Indian Journal of Case Reports, 2026)
Splenium, the posteriormost part of the corpus callosum, has the thickest collection of commissural fibers with most fibers extending into the occipital lobes; however, the exact functions are yet to be known. As such, isolated infarctions of the corpus callosum are rare due to the dual blood supply from the anterior and posterior cerebral arteries. We describe the case of a 52-year-old female who presented with a 1-week history of right-sided incongruous homonymous hemianopsia, with no other evidence of focal deficit. Neuroimaging confirmed acute infarction with intense restriction of diffusion in the left splenium involving the periventricular part. There are a few case reports available of isolated splenium infarction. There is only one case described of a splenium infarct presenting as homonymous hemianopsia, to our knowledge. Our case might shed some light on the clinical presentation in splenium infarcts, with an understanding of the visual processing pathways involving the commissural fibers.